2012
DOI: 10.1080/02607476.2012.707918
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers' reflections during field experience

Abstract: This research study investigates pre-service teachers' perceptions of their field experience in kindergartens and schools in Jordan. A total of 57 pre-service early years teachers wrote weekly reflective journals describing and commenting on their experiences during placement in kindergartens and elementary schools. Three major themes emerged from the journals: descriptive narratives of pre-service teachers' field experience, the difficulties they faced, and the advantages of their experience. In light of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…These findings resonate with earlier research (Al-Barakat, 2003;Al-Hassan et al, 2012;Flores, 2000;Flores, 2014;Flores & Day, 2006) and raise implications for improving the ITE programmes. In general, more attention needs to be given to the adequacy and coherence of the various components of ITE programme and the ways in which teacher educators view their work and role.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings resonate with earlier research (Al-Barakat, 2003;Al-Hassan et al, 2012;Flores, 2000;Flores, 2014;Flores & Day, 2006) and raise implications for improving the ITE programmes. In general, more attention needs to be given to the adequacy and coherence of the various components of ITE programme and the ways in which teacher educators view their work and role.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…They also referred to the poor quality of feedback. This supports earlier research which has identified difficulties related to supervisorsí role and feedback (Al-Barakat, 2003;Al-Hassan et al, 2012;Flores, 2014). I think that some teacher educators do not care for you as pre-service teachers and are not concerned with your future as teachers.…”
Section: The Role Of Teacher Educatorssupporting
confidence: 83%
“…This finding is in keeping with Al-Hassan et al, (2012) and Merç and Subaşı's (2015) findings that various classroom management problems are inevitable in young learners' classes. However, one potentially significant finding is that each student teacher in this study seems to have had clear ideas about how to manage young learners, and this awareness led them to develop their own strategies to overcome classroom management problems.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the importance of mathematics teachers' knowledge, and the significance of training them to be effective teachers in mathematics learning environments, research studies were conducted on conceptual understanding and pedagogical knowledge of mathematics teachers, as separate variables, around the world and in Jordan (Al-Barakat et al, 2022a;Al-Hassan et al, 2012;Al-Tarawneh, 2019;Bwalya & Rutegwa, 2023;Fraihat et al, 2022;Khasawneh et al, 2023;Mapulanga et al, 2022;Meier, 2021;Shaqar, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%